3x+6=6x+20

Simple and best practice solution for 3x+6=6x+20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+6=6x+20 equation:


Simplifying
3x + 6 = 6x + 20

Reorder the terms:
6 + 3x = 6x + 20

Reorder the terms:
6 + 3x = 20 + 6x

Solving
6 + 3x = 20 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
6 + 3x + -6x = 20 + 6x + -6x

Combine like terms: 3x + -6x = -3x
6 + -3x = 20 + 6x + -6x

Combine like terms: 6x + -6x = 0
6 + -3x = 20 + 0
6 + -3x = 20

Add '-6' to each side of the equation.
6 + -6 + -3x = 20 + -6

Combine like terms: 6 + -6 = 0
0 + -3x = 20 + -6
-3x = 20 + -6

Combine like terms: 20 + -6 = 14
-3x = 14

Divide each side by '-3'.
x = -4.666666667

Simplifying
x = -4.666666667

See similar equations:

| logbase(2x+6)144=2 | | -2(3x+2)=-48 | | Sin^2x-2cosx-2=0 | | 5(6x-4)=34x | | 10-2w=6 | | 2u+2=5p-10 | | 1+-2g=5 | | 4/15-3/15 | | 13a-1=90 | | -(6y+3)-(-5-4)=-7 | | P=4c-20+2c | | 73=4p+7 | | 2=4-2y | | F(x)=x*2+6x+15 | | -3(5s-2)-6=-3(9s+2)-5 | | -9=3k+-3 | | 2y^2-12y+8=0 | | 50=65+10t-5t^2 | | 3x^2+78=0 | | .65x+.05(14-x)=.10(-17) | | 5=a/-11 | | .18(24)+.03x=.09(18+x) | | 1/5y+11=3-3/5y | | 4x+7-9=-14 | | 6+2k=8 | | x=2.5(12.5)-26.25 | | 1=x/2-32/2*x^2 | | 5x+3=-8x+16 | | 6x^4-28x^3-10x^2=0 | | (-9x^3+9x^2-2x+4)+(4x^3+2x^2-4x-6)= | | 7x-12=2x*8 | | .375x-.2+10=.3x |

Equations solver categories